2019
DOI: 10.1371/journal.pone.0214922
|View full text |Cite
|
Sign up to set email alerts
|

Categorizing and assessing comprehensive drivers of provider behavior for optimizing quality of health care

Abstract: Inadequate quality of care in healthcare facilities is one of the primary causes of patient mortality in low- and middle-income countries, and understanding the behavior of healthcare providers is key to addressing it. Much of the existing research concentrates on improving resource-focused issues, such as staffing or training, but these interventions do not fully close the gaps in quality of care. By contrast, there is a lack of knowledge regarding the full contextual and internal drivers–such as social norms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 32 publications
(33 reference statements)
0
14
1
Order By: Relevance
“… 10–12 CHWs are often publicly admonished by punitive supervisors, compensated via incentives and honoraria (as opposed to fair wages), and receive woefully delayed payments. 6 , 13 , 14 Despite these issues, we find no evidence that low performance stems from the fact that CHWs shirk their duties. For example, in Bihar, we found that 90% of CHWs undertook the processes required to facilitate service delivery, including creating a home visit plan, surveying pregnant women and children and supporting the preparation of due lists.…”
Section: Legacy Issues: Struggles Of a Low-performance Systemcontrasting
confidence: 66%
“… 10–12 CHWs are often publicly admonished by punitive supervisors, compensated via incentives and honoraria (as opposed to fair wages), and receive woefully delayed payments. 6 , 13 , 14 Despite these issues, we find no evidence that low performance stems from the fact that CHWs shirk their duties. For example, in Bihar, we found that 90% of CHWs undertook the processes required to facilitate service delivery, including creating a home visit plan, surveying pregnant women and children and supporting the preparation of due lists.…”
Section: Legacy Issues: Struggles Of a Low-performance Systemcontrasting
confidence: 66%
“…Most often, there is only one SACMO posted and available to treat pediatric patients at the UH&FWC. Thus, the individual knowledge and opinions of this provider will influence adoption and adherence to the guidelines [37,38]. To aid these workers in identifying sick infants, the Bangladesh guidelines include a clinical algorithm for classifying signs of infection in young infants, guidance on antibiotic treatment, referral advice and follow-up [22].…”
Section: Context and Interventionmentioning
confidence: 99%
“…EthnoLab is a scenario-based behavioral decision-making game (in this case presented as a board game), with qualitative follow-up discussions, to understand the contexts, emotions, and mental models that influence decision-making. EthnoLab was developed by Final Mile Consulting and has been successfully applied in several projects across the African continent, India, and the US [ 11 , 12 ]. Content analysis of the results of EthnoLab was then used to inform the design of a CT program framework (Fig.…”
Section: Methodsmentioning
confidence: 99%